Pemanfaatan Tanaman Obat Keluarga (TOGA) sebagai Upaya Swamedikasi melalui Pembuatan Minuman Immunostimulan - Madyawati Latief; Indra Lasmana Tarigan; Nindita Clourisa Amaris Susanto; Anggit Prima Nugraha; Niken Rarasati (Universitas Mathla'ul Anwar Banten, 2022)
UTILIZATION OF FAMILY MEDICAL PLANTS (TOGA) AS SELF-MEDICATION EFFORTS THROUGH MAKING IMMUNOSTIMULANT DRINKS. Family Medicinal Plants (TOGA) are plants that are grown at home and have medicinal properties. Apart from being a medicine, TOGA can have other benefits such as a family nutrition enhancer, cooking spice, or what is famous for its empon-empon and beauty enhancer. The scientific benefits of TOGA can be carried out through the empowerment of the Community Development and Family Welfare Organization (PKK) group. PKK aims to empower women to become independent women and be able to foster families with the scientific benefits of TOGA which can be done through empowering community organization groups for Family Development and Welfare (PKK). PKK aims to empower women to become independent women and be able to foster families through the use of TOGA as a family health product to self-medicate the community to build immunity, especially during the Covid-19 pandemic, efforts to increase body immunity are needed in addition to implementing health protocols.